31.0k views
5 votes
PLEASEE HELP

FIRST ONE IS QUESTION THE REST ARE CHOICES
What is the following difference?

PLEASEE HELP FIRST ONE IS QUESTION THE REST ARE CHOICES What is the following difference-example-1
PLEASEE HELP FIRST ONE IS QUESTION THE REST ARE CHOICES What is the following difference-example-1
PLEASEE HELP FIRST ONE IS QUESTION THE REST ARE CHOICES What is the following difference-example-2
PLEASEE HELP FIRST ONE IS QUESTION THE REST ARE CHOICES What is the following difference-example-3
PLEASEE HELP FIRST ONE IS QUESTION THE REST ARE CHOICES What is the following difference-example-4
PLEASEE HELP FIRST ONE IS QUESTION THE REST ARE CHOICES What is the following difference-example-5

2 Answers

7 votes
2ab (cube root(192ab^2)) - 5 (cube root(81a^4b^5))
First simplify the radicals.
cubert (192) = (4*4*4*3) = 4cubert(3)
cubert (81) = (3*3*3*3) = 3cubert(3)
8ab cubert(3ab^2) - 15ab cubert(3ab^2)
- 7ab cubert (3ab^2)
Option 4
User Randy Stegbauer
by
5.3k points
3 votes

2ab( \sqrt[3]{192ab^2} )-5( \sqrt[3]{81a^4b^5} )=2ab( \sqrt[3]{4^3*3*ab^2} )-5( \sqrt[3]{3^3*3*a^4b^5} )= \\ \\ =2ab(4 \sqrt[3]{3ab^2} )-5( 3ab\sqrt[3]{3ab^2} )=8ab(\sqrt[3]{3ab^2} )- 15ab(\sqrt[3]{3ab^2} )= \\ \\ =(8ab-15ab)(\sqrt[3]{3ab^2})=-7ab(\sqrt[3]{3ab^2})
User Stefaan Colman
by
5.9k points